2017
DOI: 10.1111/psyp.13041
|View full text |Cite
|
Sign up to set email alerts
|

An adaptive orienting theory of error processing

Abstract: The ability to detect and correct action errors is paramount to safe and efficient goaldirected behaviors. Existing work on the neural underpinnings of error processing and post-error behavioral adaptations has led to the development of several mechanistic theories of error processing. These theories can be roughly grouped into adaptive and maladaptive theories. While adaptive theories propose that errors trigger a cascade of processes that will result in improved behavior after error commission, maladaptive t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
262
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(291 citation statements)
references
References 157 publications
(259 reference statements)
25
262
4
Order By: Relevance
“…For nearly three decades, psychophysiologists have studied a specific neural response to error commission, referred to as the error-related negativity (ERN or Ne;Falkenstein, Hohnsbein, & Hoormann, 1990;Gehring, Goss, Coles, Meyer, & Donchin, 1993, 2018. The ERN is elicited when participants make errors (i.e., motor slips) in forced-choice speeded-response tasks.…”
Section: Negativit Ymentioning
confidence: 99%
“…For nearly three decades, psychophysiologists have studied a specific neural response to error commission, referred to as the error-related negativity (ERN or Ne;Falkenstein, Hohnsbein, & Hoormann, 1990;Gehring, Goss, Coles, Meyer, & Donchin, 1993, 2018. The ERN is elicited when participants make errors (i.e., motor slips) in forced-choice speeded-response tasks.…”
Section: Negativit Ymentioning
confidence: 99%
“…We have suggested that the computational goal of this generative system is thus not specific to learning and is instead a more generic orienting system involved in signaling the need for cognitive control (Cavanagh & Frank, 2014). A generic orienting response can then invoke adaptive control processes (see Wessel, 2018), possibly due to theta band phase-based coupling between brain regions (Cavanagh, Cohen, & Allen, 2009; see Figure 3a). It is fair to call out the irony within this definition, since cognitive control is a psychological term.…”
Section: Computational Goalsmentioning
confidence: 99%
“…From this perspective, errors might be considered maladaptive, as they derail ongoing behaviors. While these two strands of the literature—those focusing on adaptive responses and those focusing on maladaptive responses—have proceeded relatively independently, Wessel ( ) proposes a theory designed to integrate the two. He argues that errors cause a disruption or halting of ongoing behavior, consistent with the maladaptive theories.…”
Section: Adjustments Of Controlmentioning
confidence: 99%
“…With regard to the neural underpinnings, Wessel ( ) cites work suggesting that an inhibition network consisting of regions of the presupplementary motor area, right inferior frontal gyrus, and subthalamic nucleus of the basal ganglia are involved in the disruption of behavior. Van Campen, Kunert, van den Wildenberg, & Ridderinkof ( ) present evidence using transcranial magnetic stimulation (TMS) of the critical role of right inferior frontal gyrus in the suppression of such action tendencies.…”
Section: Adjustments Of Controlmentioning
confidence: 99%